2004
DOI: 10.4028/www.scientific.net/msf.467-470.27
|View full text |Cite
|
Sign up to set email alerts
|

Study of Deformation Microstructure and Static Recovery in Copper after Cold Drawing

Abstract: The analysis of the microstructure deformation and the static recovery were investigated by transmission electron microscopy (TEM) observations, after cold drawing in copper. The observed microstructures according to the orientation of grains are composed of dislocation cells, deformation bands and dense dislocation walls. In <001> grains, the cells are equiaxed, regular and surrounded by sharp walls, whereas in the <111> grains the cell creation is also in progress. During the annealing, the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This is because previous studies of low strains have shown for both single crystals and polycrystals that the grain orientation significantly affects the morphology, the structural parameters, and the stored energy of the deformed structure. [17][18][19][20] To study such an effect after a large strain, a true rolling strain of 2 has been chosen for a material that had an initial grain size of about 75 m. At this strain, rolling texture components with typical large-strain lamellar deformation structures have developed, but the width of structural features with a given orientation may still be sufficient to allow an examination of a correlation of the local deformation microstructure with a given texture component.…”
Section: Introductionmentioning
confidence: 99%
“…This is because previous studies of low strains have shown for both single crystals and polycrystals that the grain orientation significantly affects the morphology, the structural parameters, and the stored energy of the deformed structure. [17][18][19][20] To study such an effect after a large strain, a true rolling strain of 2 has been chosen for a material that had an initial grain size of about 75 m. At this strain, rolling texture components with typical large-strain lamellar deformation structures have developed, but the width of structural features with a given orientation may still be sufficient to allow an examination of a correlation of the local deformation microstructure with a given texture component.…”
Section: Introductionmentioning
confidence: 99%
“…When using an experimental initial microstructure characterized by EBSD these simulations give the best results (in terms of recrystallization microstructure and texture) with the hypothesis that nuclei are formed on sites with the highest stored energy [6,7]. However, this hypothesis is in disagreement with the recent experimental observations [8][9][10] which have shown that the orientations with the low stored energy preferentially develop. This apparent disagreement is related to the scale factor: the EBSD resolution disables the internal structure of subgrains.…”
mentioning
confidence: 83%
“…1. The parameters used for the nucleation kinetics modeling of the different texture components were estimated (see [19] for details) from the results of TEM observations of the first recrystallization stages of these materials [8,9]. For IF Ti steel the recovery of {111}<110> subgrains is estimated to be the most rapid so that the nucleation on such a site begins earlier than for other orientations; for cold drawn copper the first nuclei are expected for the orientations {100}<uvw>.…”
Section: Application Of the Modelmentioning
confidence: 99%
“…43 shows the fatigue crack growth of the MP35N material subjected to different stress ratios, as can be seen, increase of stress ratio does shift the curve slightly to the right, thus contributing to increased crack growth in the material, but the variance observed for the two different stress ratios did not change significantly. The final ΔK at catastrophic fracture approached and exceeded 100MPa m 1/2 which is an evidence of high fracture toughness in the material.…”
mentioning
confidence: 83%
“…understand the mechanics [23,[30][31][32][33][34][35] involved during the wire drawing process. Based on the prior research findings, it can be concluded that the amount of plastic deformation or the total reduction significantly influences the mechanical properties [10,23,26,32,[36][37][38], work hardening [34,39,40], hardness distribution [28,29,31,41,42], and also on the texture and microstructural characteristics of the wire [18,20,21,[43][44][45][46][47][48][49][50][51] .…”
Section: Several Researchers Have Reported Numerous Analytical Theorimentioning
confidence: 99%